(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Chronic venous insufficiency (CVI) is an advanced stage of chronic venous disease characterized by edema, skin changes, and venous ulceration. The most common etiology is chronic superficial venous insufficiency of the lower extremities involving the great and small saphenous veins. Endovenous laser ablation (EVLA) under ultrasound guidance has been widely applied because of its minimally invasive nature, safety, and high therapeutic efficacy. However, conventional EVLA and surgical techniques commonly destroy or remove the entire saphenous vein. We report the outcomes of a modified ultrasound-guided EVLA technique based on venous mapping, aiming to selectively ablate reflux sites while maximally preserving the saphenous vein. Case series: Ten patients diagnosed with chronic superficial venous insufficiency of the lower extremities, CEAP class C2–C3, were included based on clinical manifestations and duplex Doppler ultrasound findings. All patients underwent modified ultrasound-guided endovenous intervention using a 1940-nm diode laser system. The procedure targeted only refluxing venous segments identified on venous mapping while preserving unaffected portions of the great saphenous vein. Results: Clinical symptoms improved markedly from the first postoperative week. Pain, numbness, and edema almost completely resolved, while >90% of varicose veins collapsed. Follow-up duplex Doppler ultrasound demonstrated preserved bilateral great saphenous vein patency in approximately 80% of treated segments without residual reflux. Continued improvement was observed at 6-month and 1-year follow-up visits, with no clinical recurrence recorded. No perioperative complications or major adverse events were observed. Conclusions: Modified ultrasound-guided EVLA using a 1940-nm diode laser appears to be a safe, effective, and minimally invasive treatment for CEAP C2–C3 chronic superficial venous insufficiency. This technique minimizes pain, bruising, and recovery time while preserving up to 80% of the great saphenous vein without compromising treatment efficacy. It may represent a promising alternative to conventional destructive techniques by reducing operative time, decreasing anesthetic requirements, improving postoperative comfort, and maintaining the saphenous vein as a potential autologous conduit for future coronary or peripheral bypass surgery if needed.